ChemInform Abstract: Decarboxylative Mannich Reactions. Issue 30 (4th July 2013) - Boehm, Maximillian; Proksch, Kerstin; Mahrwald, Rainer
Abstract The reaction of various aromatic and aliphatic imines with β‐keto carboxylic acids does not require any catalyst.